Mechanisms underlying cognitive impairment and management strategies in type 2 diabetes - Chen, Xiaolin; Huang, Yan; Xiong, Xiaoxing (Frontiers in Endocrinology, 2025)
Type 2 diabetes (T2D) is increasingly recognized as a risk factor for cognitive impairment, ranging from mild cognitive impairment (MCI) to dementia. The underlying mechanisms involve a complex interplay of hyperglycemia, insulin resistance, neuroinflammation, oxidative stress, vascular dysfunction, and amyloid pathology. Effective management strategies remain an area of active investigation. This review explores the pathophysiological mechanisms linking T2D to cognitive dysfunction and evaluates current and emerging therapeutic strategies to preserve cognitive function in diabetic patients. Chronic hyperglycemia and insulin resistance impair neuronal function and synaptic plasticity, while microvascular complications contribute to cerebral hypoperfusion and white matter lesions. Additionally, metabolic disturbances exacerbate neurodegenerative processes, further compromising cognitive health. Effective management strategies for cognitive impairment in T2D include regular cognitive screening, stringent glycemic control, lifestyle modifications, comprehensive cardiovascular risk management, patient education and pharmacological interventions such as metformin, GLP-1 receptor agonists (GLP1RAs), and sodium-glucose cotransporter 2 (SGLT2) inhibitors, which may offer neuroprotective benefits. In this review, we conclude that cognitive impairment in T2D results from complex, interrelated mechanisms requiring early intervention and personalized strategies. While current therapies focus on metabolic and vascular risk reduction, future research should prioritize biomarker discovery, mechanism-driven treatments, and long-term clinical trials to optimize outcomes. A proactive, integrated care model is essential to mitigate cognitive decline in this high-risk population.